LOWER LEVELS OF VITAMIN D CORRELATE WITH CLINICAL DISEASE ACTIVITY AND QUALITY OF LIFE IN INFLAMMATORY BOWEL DISEASE - Francisca DIAS DE CASTRO; Joana MAGALHÃES; Pedro BOAL CARVALHO; Maria João MOREIRA; Paula MOTA; José COTTER (Arquivos de Gastroenterologia, 2015)
Background - Inflammatory bowel disease, comprising Crohn's disease and ulcerative colitis, is a group of debilitating conditions associated with deregulated mucosal immune response. Vitamin D has been implicated in immune response and gastrointestinal function. Objectives - To investigate the correlation between serum vitamin D levels and disease activity and quality of life in patients with inflammatory bowel disease. Methods - This cross-sectional study enrolled ambulatory patients with inflammatory bowel disease and assessed clinical disease activity and quality of life (Short Inflammatory Bowel Disease Questionnaire [SIBDQ]). Vitamin D levels were determined via serum 25-hydroxyvitamin D measurement; deficiency was defined as values <20 ng/mL. Statistical analysis was performed with SPSS vs 20.0. Results - A total of 76 patients were enrolled, 19 with ulcerative colitis (25%) and 57 with Crohn's disease (75%). Overall, mean serum 25-hydroxyvitamin D levels were low (26.0±10.0 ng/mL), while those in patients with Crohn's disease were significantly lower than ulcerative colitis (24.6±8.0 vs 30.0±12.5 ng/mL; P=0.032). Vitamin D deficiency was found in 30% of patients. Patients who were in clinical remission were found to have higher levels of vitamin D than those who were not in remission (28.0±10.3 vs 21.6±6.0 ng/mL, P=0.001). Inflammatory bowel disease patients with SIBDQ scores <50 were found to have significantly lower mean vitamin D levels compared with patients who had SIBDQ scores ≥50 (23.4±6.9 vs 27.9±10.8 ng/mL, P=0.041). Conclusions - A high proportion of patients with inflammatory bowel disease were vitamin D deficient, particularly patients with Crohn's disease. Both clinical disease activity and quality of life correlated significantly with lower levels of vitamin D, illustrating a clear need for supplementation in patients with inflammatory bowel disease.